Three new species of the genus Suctobelbella (Acari: Oribatida: Suctobelbidae) from Sanjiang Plain, Northeast China - Liu, Dong; Wu, Donghui (Zootaxa, 2013)
Three new species of the genus Suctobelbella from Sanjiang Plain in Northeast China are described: S. triangulata sp. nov., S. obtusa sp. nov., S. sanjiangensis sp. nov., and a key to all known species of China is provided.